Inhibition of MHC II Gene Transcription by Nitric Oxide and Antioxidants - Harari, Olivier (2004)
MHC class II molecules are expressed on the surface of antigen presenting cells and are loaded with peptides processed from the phagosomal compartment of these cells. Such complexes interact with the CD4 positive T lymphocyte receptor for antigen and a strong interaction is followed by T cell activation and proliferation. As class II expression is critical for antigen specific immunity its expression mostly restricted to a few cell types but can be induced on others in response to interferon γ. This expansion of antigen presenting ability plays a role in increasing the duration and intensity of the immune response. Nitric oxide and antioxidants attenuate this class II induction through negative effects on the induction of class II transactivator protein expression and on the binding of transcription factor NF-Y to the class II promoter.